Formulation of Nanoemulgel Preparation from Jernang Resin Extract (Daemonorops draco (Wild.)) for Healing Burn Wounds in Male White Rats (Rattus norvegicus) - Yulia Sari, Ersa; Cut Mutia; Fitri, Zahwa Syuhada; R.A. Talitha Nabila Sakhi; Indri Maharini; Elisma (Jurnal FARMASIMED (JFM), 2025)
Background: Jernang resin (Daemonorops draco) contains secondary metabolite compounds, namely flavonoids, alkaloids, triterpenoids and steroids that play a role in the healing process of burns. Objective: The development of jernang resin into a pharmaceutical dosage form can be done in the form of nanoemulgel. Nanoemulgel is easy to apply to the skin, and can be specifically targeted to the site of treatment, avoiding first metabolism, and reducing gastric or systemic side effects. Method: the method used is experimental using a Completely Randomized Design (CRD) with a Post Test Only Control Group Design approach using 25 male white rats consisting of 5 treatment groups: positive control (bioplacenton), negative control (vaseline flavum) F1 1%, F2 3%, F3 5%. The parameters observed were the physical properties of nanoemulgel and the effectiveness of burns on male white rats, namely burn diameter, wound healing percentage, collagen density and fibroblast cells through histological observations. Results: each treatment has effectiveness, The best burn healing effectiveness is in F3 5% with a healing percentage of 93.32% and very dense collagen and fibroblast cells among other treatment groups, followed by F1 1% with a healing percentage of 90.65% and dense collagen density, the effectiveness produced is the same as the positive control (bioplacenton) which is with a burn healing percentage of 90.77%, and the concentration with the lowest effect is in F2 3% with a burn healing percentage of 84.14%. Conclusion: Nanoemulgel with different concentrations does not affect the physical properties of nanoemulgel but has different burn healing effects, with the best concentration being 5% jernang resin extract.